Organic and Biofertilizers as Replacements for Synthetic Fertilizers to Increase Rice Yield in Tidal Swamp - Abduh, Andin Muhammad; Masganti, Masganti; Sari, Nukhak Nufita; Haris, Abdul; Ifansyah, Hairil; Mulyawan, Ronny (Green Engineering Society, 2024)
Maintaining soil sustainability to increase and sustain land productivity can be achieved by minimizing synthetic fertilizers and maximizing organic fertilizers and biofertilizers, especially in suboptimal lands. Therefore, this study aimed to determine the effects of organic fertilizers and biofertilizers with reduced NPK (Nitrogen, Phosphate, Potassium) dosage on increasing rice yield in tidal swamp areas in Tebas Sungai Village, West Kalimantan. The procedures were carried out using a complete randomized block design, with several treatments consisting of 175 kg ha-1 NPK as a control (P0), 130 kg ha-1 NPK + 1.5 tons ha-1 cow manure (P1), 130 kg ha-1 NPK + 3.0 tons ha-1 cow manure (P2), and 130 kg ha-1 NPK + 25 kg ha-1 biofertilizers (P3). Based on assessment, the study area was then categorized as C overflow type. The results showed that the combination of NPK synthetic fertilizers with cow manure led to a 15.1%, 25%, 5.6%, and 5.4% increase in total tillers, total grains per panicle, weight of 1000 grains, and rice yield, respectively. In addition, the use of NPK fertilizers with biofertilizers increased total tillers, total grains per panicle, weight of 1000 grains, and rice yield by 24.6%, 56%, 7.7%, and 18%, respectively, compared to only NPK fertilizers. Based on these results, improving rice performance in tidal swamp areas could be achieved by integrating organic or biofertilizers with synthetic fertilizers.